THE COST PRICE OF GROWING LAVENDER (LAVANDULA OFFICINALIS) AND THE ECONOMIC EFFICIENCY OF ITS PROCESSING IN THE TERRITORY OF THE FEDERATION OF BOSNIA AND HERZEGOVINA (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Lavender is one of the Lamiaceae family’s most famous ornamental, aromatic, and medicinal plants. It is widely used in the cosmetic, pharmaceutical and food industries and is an excellent honey plant. The plantation cultivation of lavender in BiH is still not as developed as in other countries. Still, an increasing number of farms and specialized farms recognize this culture’s potential. Given the need for more research on the economic results of growing lavender in Bosnia and Herzegovina, this research aims to analyze the cost of growing fresh lavender and the economic efficiency of its processing. Primary data was collected with the help of surveys conducted on four farms, focusing on the necessary investments and operational costs of growing lavender and the income from the sale of dried flowers. The results showed that the cost of growing 1 kg of fresh lavender flowers ranges from 0.71 BAM to 1.33 BAM, which indicates significant differences between the observed farms. Lavender processing also showed different levels of economy among farms. According to this research, cultivating lavender in Bosnia and Herzegovina is an economically profitable option; however, it is necessary to research a more significant number of farms. Also, due to different applied agricultural techniques in the cultivation of lavender, economic results differ significantly from farm to farm, so one of the research recommendations is additional education of producers in this area to increase the economic efficiency of these farms with the improvement of production technology.